Effect of a Humanized Diet Profile on Colonization Efficiency and Gut Microbial Diversity in Human Flora-Associated Mice - Dong, Sashuang; Zeng, BenHua; Hu, Ling; Zhang, Yuling; Xiong, Jiaqi; Deng, Jing; Huang, Liyan; Liao, ZhenLin; Wang, Jie; Wei, Hong; Fang, Xiang (Frontiers in Nutrition, 2021)
Human flora-associated (HFA) mouse models allow us to design interventions for human disease research to test specific hypotheses and explore the complex commensal microbiome while avoiding the ethical limitations of using humans as models to directly study intestinal flora diseases. However, few studies have investigated the effect of a humanized diet profile (coarse-feed diet; CFD) on colonization efficiency and gut microbial diversity in HFA mice. We tested the colonization efficiency and gut microbial diversity in germ-free Kunming (KM) mice fed a CFD or a purified feed diet (PFD) at 1, 2, and 4 weeks. Although the colonization efficiencies differed significantly (67.50–70.00% vs. 72.69–85.96%) in the HFA mice, the colonization efficiency of the PFD-fed HFA mice (85.96%) was significantly higher than that of the CFD-fed mice (69.61%) at 2 weeks. At 4 weeks, the colonization efficiency of the PFD-fed mice (72.69%) was comparable to that of the CFD-fed mice (70.00%). Additionally, the gut microbial diversity of the CFD-fed HFA mice was similar to that of a human fecal donor. Regarding the Kyoto Encyclopedia of Genes and Genomes colonic microbiota metabolic pathways, the CFD-fed HFA mice showed more similarities to the human donor than to the PFD-fed mice in amino sugar and nucleotide sugar metabolism, biosynthesis of amino acids, carbon metabolism, purine metabolism, and phosphotransferase systems. In conclusion, the humanized diet profiles of the CFD and PFD could help establish human microbiotas in mice. Constructing HFA mouse models fed a CFD for 4 weeks may be useful in researching human-derived intestinal diseases.